Erzurum’un Şenkaya İlçesine Bağlı Ormanlı Köyünde Bulunan Erken Dönem Türk Kültürüne Ait İnsan Biçimli Taş Heykeller ve Balballar - Yavuz GÜNAŞDI; Ahmet Cüneydi HAS; Burak BİNGÖL (Gazi Akademik Bakış)
The Eastern Anatolia Region has been the first stop for the tribes coming to Anatolia from Eurasia. The wide plateaus and water resources in the region, which is a mountainous geography, have made this region a center of attraction for equestrian nomadic cultures that live on sheep and goats since ancient times. Although the Caspian Sea was a natural obstacle for these tribes who wanted to enter Anatolia from Central Asia, these cultures entered Anatolia using the Caucasus in the north and the Zagros in the south. These cultures left behind many cultural elements such as kurgans-graves, stamps-heaps, runic writings, rock paintings, toponyms and stone statues-balbals. In the article, Şenkaya Stone statues and balbals, which are among these elements, were examined. Stone sculptures were depicted and their motifs were evaluated, and then they were dated by comparing them with the Anatolian and Eurasian stone sculpture tradition.